Investigation of a novel heat pipe solar collector/CHP system - Zhao, Xudong (2003)
The European Union has an ongoing commitment to reducing CO2 emission as highlighted by its agreement at the Kyoto Summit. One approach to achieving these reductions would be to develop alternative energy sources for major energy demanding sectors. In the EU, about 40% of all energy consumed is associated with buildings and of this, about 60% is utilised in the housing sector. A major part of the energy demand of buildings could be met by utilising renewable energy sources, e.g. solar energy.